Engineered nano-bio interfaces for intracellular delivery and sampling: Applications, agency and artefacts. (March 2020) - Lestrell, Esther; Patolsky, Fernando; Voelcker, Nicolas H.; Elnathan, Roey
Graphical abstract: Abstract: Engineered nano-bio cellular interfaces bring together well-defined nanoscale material morphologies with organic living systems. These extraordinarily complex interfaces are set to produce radical advances in the life sciences, through fundamental research in the emerging multidisciplinary field of cellular nano-biotechnology. We examine the role of a particular class of nanostructured platform: vertically aligned nanowire (VA-NW) arrays. These arrays feature diverse nanoscale topographies that enable unprecedented manipulation of cell functions and processes in vivo, in situ and in vitro . While the platform still requires further optimisation, recent use of the arrays – for in vivo transfection, non-destructive intracellular sampling and to gain fundamental insights into cellular responses to extracellular topographic cues – effectively demonstrates the platforms' potential. We review innovative applications that show the repertoire of VA-NW arrays as highly efficient, universal, scalable intracellular delivery and sampling platforms, which presage prospects for clinical translation. We analyse the mechanisms by which VA-NW arrays facilitate delivery of bioactive cargos, and discuss the state of current knowledge about effects of nanowire topography on the cell-nanowire interface.